Use of social media for educational services promotion - Kolomatskyi, Artem; Pavlíček, Antonín, 1977-; Havlík, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
The aim of the thesis is to analyze the influence of the promotion in the social media for educational services. Current work covers all the definitions and overviews of the literature that is relevant for the understanding of the chosen topic. Theoretical data was followed by the examples of implementation of tools that could help the enterprises to promote the goods and services on the local market. The practical part of the thesis is standing on the research of the business that provides educational services in Ukraine and how investments in the development of social media tools are showing the rise of the sales for the company. I consider my work to be helpful in understanding all crucial areas in social media marketing. The aim of this study is to offer valuable insights into the development campaign process that would help Meat Studies to attract more students to educational services of the company.
Vedoucí práce: Antonín Pavlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses